Profil penyakit kulit pada pelajar sekolah asrama di Kabupaten Magelang, Jawa Tengah - Tuntas Rayinda; Devi Artami Susetiati; Sri Awalia Febriana (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Individuals who live in boarding schools often experience various skin diseases, both infection and non-infectious because of exposure to various risk factors such as hormonal changes, poor hygiene and sanitation, and dense living quarters. To date, data on the prevalence of disease in adolescents in boarding schools are still very limited. This study is an observational cross-sectional study that aims to describe skin diseases that often occur in adolescents who live in boarding schools. Surveys and clinical examinations are carried out by dermatologist. Based on a survey of 1,250 students aged 10 - 16 years, 1,073 students (85.8%) had at least one skin disease. A total of 1,073 cases from 27 different types of skin diseases were found in these students. The five most common skin diseases are dermatophytosis, scabies, acne vulgaris, ecthyma, and pityriasis versicolor. Education, periodic surveys, mass treatment, and interventions to improve hygiene and living conditions are key to success in the management of skin diseases in students living in boarding schools.